Study Engagement and Burnout of the PhD Candidates in Medicine: A Person-Centered Approach - Tikkanen, Lotta; Pyhältö, Kirsi; Bujacz, Aleksandra; Nieminen, Juha (Frontiers in Psychology, 2021)
This study focused on exploring individual variations in doctoral candidates’ well-being, in terms of experienced research engagement and burnout by using a person-centered approach. In addition, the associations between well-being profiles and gender, country of origin, study status (full-time or part-time), research group status and drop-out intentions were explored. The participants were 692 PhD candidates in the field of medicine. Latent profile analysis was employed to identify the well-being profiles. Four distinct profiles were identified: high engagement–low burnout, high engagement–moderate burnout, moderate engagement–moderate burnout, and moderate engagement–high burnout. Working in a clinical unit or hospital and working in a research group seemed to be related to increased engagement and reduced risk for suffering burnout, while the intentions to quit one’s doctoral studies were more frequently reported in profiles with moderate levels of engagement. The findings imply that although a significant number of PhD candidates in medicine had an increased risk for developing burnout, for most of the PhD candidates research education is an engaging experience.